Enhancing Students' Curiosity using e-Atlas PBL Integrated with Yogyakarta's Local Wisdom on Biodiversity Topic - Muhammad Rasyid; Habibatul Unayah; Tien Aminatun; Asri Widowati; Ibrahim Pandu Ame (Jurnal Inovasi Pendidikan IPA, 2026)
Curiosity is a critical competency in science education, fostering deeper understanding and problem-solving skills. This study aimed to develop and evaluate a problem-based learning (PBL) e-Atlas integrated with Yogyakarta's local wisdom to enhance students' curiosity in biodiversity material. Using the 4-D model (Define, Design, Develop, Disseminate), this research focused on creating an innovative learning tool tailored to address the lack of laboratory resources in schools and promote active learning. The e-Atlas combines interactive digital features with cultural and ecological relevance, enabling students to engage in virtual activities. The product was validated by four experts (media, content, and practitioners), achieving an Aiken's V index of 0.97, categorized as "very high." A readability test involving 10 ninth-grade students yielded a 96% approval rate, indicating the e-Atlas was user-friendly and engaging. The effectiveness of the tool was tested through a one-group pretest-posttest design with 30 students. Results showed a significant improvement in curiosity, with an N-gain score of 0.71, classified as "high." Additionally, a field test was conducted with 30 students in a control class and 30 students in an experimental class. The experimental class, which used the e-Atlas, showed a greater increase in curiosity and engagement compared to the control class, highlighting the tool's effectiveness in fostering active learning.This study concludes that the e-Atlas is a valid, practical, and effective tool for enhancing students' curiosity. By integrating local wisdom into a problem-based framework, the e-Atlas provides meaningful and contextualized learning experiences. This research highlights the potential of technology-enhanced learning tools to bridge educational gaps, promote critical thinking, and instill environmental awareness among students. Further dissemination of this tool could contribute significantly to modernizing science education in Indonesia and beyond.